Optical solitons and stability analysis with spatio-temporal dispersion in Kerr and quadric-cubic nonlinear media - Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru (Elsevier Gmbh, 2019)
In this work, we investigate the optical solitons to the nonlinear Schrodinger equation (NISE) with spatio-temporal dispersion (STD) arising in ferromagnetic materials and optical fiber. The integration technique adopted is the Sine-Gordon expansion method (SGEM). In addition, the stability analysis of the model is performed.
Keywords: Sine-Gordon expansion method; Solitons; Modulation instability analysis